THE IMPACT OF RETURN ON ASSETS, INSTITUTIONAL OWNERSHIP, AND FIRM SIZE ON TAX AVOIDANCE IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ciptawan, Ciptawan; Lim, Sheryn (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
Taxes play a huge role as the state’s main income to develop a country, these funds come from tax payments by taxpayers. Since taxes are used for the country’s well-being, government strive to receive as much amount of tax as possible, while taxpayers try to minimize tax payments as it is viewed as burden that decreases their net income, this practice is known as tax avoidance. Thus, there are a few key factors discussed in this study, namely return on assets, institutional ownership, and firm size on how they impact tax avoidance, focusing on Property and Real estate companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2022. Purposive sampling method is used as sampling technique in this study. From a population of 86 property and real estate companies, 25 of them are used as sample by adopting quantitative research design and utilizing secondary data, which are financial statements published on Indonesia Stock Exchange. Method of data analysis is carried out using multiple linear regression, processed through IBM SPSS version 26. The result of this study shows that return on assets has significant impact on tax avoidance, while institutional ownership and firm size does not have significant impact on tax avoidance. Simultaneously, all three independent variables have significant impact on tax avoidance.